Differentiation during fig ontogeny suggests opposing selection by mutualists - Silvia B. Lomáscolo (Wiley, 2020)
Abstract Dioecy allows separation of female and male functions and therefore facilitates separate co‐evolutionary pathways with pollinators and seed dispersers. In monoecious figs, pollinators' offspring develop inside the syconium by consuming some of the seeds. Flower‐stage syconia must attract pollinators, then ripen and attract seed dispersers. In dioecious figs, male (“gall”) figs produce pollen but not viable seeds, as the pollinators' larvae eat all seeds, while female (“seed”) figs produce mostly viable seeds, as pollinators cannot oviposit in the ovules. Hence, gall and seed figs are under selection to attract pollinators, but only seed figs must attract seed dispersers. We test the hypothesis that seed and gall syconia at the flower stage will be similar, while at the fruiting stage they will differ. Likewise, monoecious syconia will be more similar to seed than gall figs because they must attract both pollinators and seed dispersers. We quantified syconium characteristics for 24 dioecious and 11 monoecious fig species and recorded frugivore visits. We show that seed and gall syconia are similar at the flower stage but differ at the fruit stage; monoecious syconia are more similar to seed syconia than they are to gall syconia; seed and gall syconia differentiate through their ontogeny from flower to fruit stages; and frugivores visit more monoecious and seed syconia than gall syconia. We suggest that similarity at the flower stage likely enhances pollination in both seed and gall figs and that differentiation after pollination likely enhances attractiveness to seed dispersers of syconia containing viable seeds. These ontogenetic differences between monoecious and dioecious species provide evidence of divergent responses to selection by pollinators and seed dispersers.